Synthesis and Evaluation of Pyrimidine Steroids as Antiproliferative Agents - Alejandra Cortés-Percino; José Luis Vega-Báez; Anabel Romero-López; Adrián Puerta; Penélope Merino-Montiel; Socorro Meza-Reyes; José M. Padrón; Sara Montiel-Smith (Molecules, 2019)
A small and focused library of steroidal non-fused and fused pyrimidines was prepared from pregnenolone acetate and diosgenin, respectively. The key step was the cycloaddition reaction of nitrogen-containing 1,3-binucleophiles with the steroidal α,β-unsaturated ketone. Urea, thiourea and guanidine reacted in a similar manner and afforded the steroidal pyrimidines in good yields. The antiproliferative tests against human tumor cell lines gave GI50 values in the micromolar range and had no effect on healthy fibroblasts. Additional experiments indicated that the compounds did not act as P-glycoprotein substrates, thus avoiding the rise of drug resistance. The fused steroidal pyrimidinethione was selected as drug lead for further testing due to its strong antiproliferative activities within the low micromolar range.